Mixed and disseminated paracoccidioidomycosis after liver transplantation: Case report - Sinkos, Camila [UNESP]; Grillo, Thais Gagno [UNESP]; Bonini, Ana Clara Muraro [UNESP]; Cardoso, Lucas Gonçalves [UNESP]; Watanabe, Erika Mayumi [UNESP]; Cavalcante, Ricardo de Souza [UNESP]; Silva, Giovanni Faria [UNESP]; Yamashiro, Fabio da Silva [UNESP]; Romeiro, Fernando Gomes [UNESP]; Lima, Talles Bazeia [UNESP] (Elsevier, 2021)
Paracoccidioidomycosis (PCM) is a systemic granulomatous fungal infection rarely associated with solid organ transplantation. We report the second case of PCM in an adult after liver transplantation. A 47-year-old woman who had undergone liver transplantation was hospitalized for flu-like symptoms and multiple erythematous ulcerated skin papules. There was lymphadenopathy, pulmonary compromise, and quickly progression to septic shock. PCM was confirmed by skin biopsy and serologic tests, and a satisfactory response to amphotericin B was achieved.
Keywords: Cutaneous disease; Immunosuppression; Liposomal amphotericin B; Liver transplantation; Paracoccidioidomycosis